GIBBERELLIC ACID REDUCES FLOWERING AND TIME OF MANUAL THINNING IN ‘MACIEL’ PEACH TREES - MARCOS ANTÔNIO GIOVANAZ (Revista Brasileira de Fruticultura, 2016)
ABSTRACT The thinning peach fruits is to reduce the load of the plant with the aim to improve the size, flavor and color of the remaining fruits. However, the practice of thinning requires high demand of manpower and become more expensive the production costs. The objective of this study was to evaluate the reduction of flowering buds and the time of hand thinning in ‘Maciel’ peach after gibberellic acid (GA3) application at different times and concentrations. The experiments were performed in the harvests of 2012 and 2013 in a commercial peach orchard located in the county of Morro Redondo, RS. The plants of cultivar Maciel, in 2012, were sprayed with four doses of GA3 0, 25, 75 and 125 mg L-1, at different times 20, 40 and 60 days after full bloom (DAFB). The number of flowering buds and consequently thenumber of flowers was reduced in the 2013 season after application of GA3 on the 2012 harvest. The manual thinning decreased with doses applied at 60 DAFB. The number of flowering buds and consequently the number of flowers was reduced in 2013. There was reduction of manual thinning when applied at 60 DAFB. The doses of 25, 75 and 125 mg L-1 applied at 60 DAFB resulted in a reduction of 50.1, 76.9 and 87.1%, respectively, at the time of hand thinning. When applied the dose of 25 mg L-1 of GA at 60 DAFB reduces the number of flowering buds and hand thinning time in the next cycle in ‘Maciel’ peach, without compromising production.